Reorganisation of chromatin during erythroid differentiation - A. A. Khabarova; A. S. Ryzhkova; N. R. Battulin (Вавиловский журнал генетики и селекции)
A totipotent zygote has unlimited potential for differentiation into all cell types found in an adult organism. During ontogenesis proliferating and maturing cells gradually lose their differentiation potential, limiting the spectrum of possible developmental transitions to a specific cell type. Following the initiation of the developmental program cells acquire specific morphological and functional properties. Deciphering the mechanisms that coordinate shifts in gene expression revealed a critical role of three-dimensional chromatin structure in the regulation of gene activity during lineage commitment. Several levels of DNA packaging have been recently identified using chromosome conformation capture based techniques such a Hi-C. It is now clear that chromatin regions with high transcriptional activity assemble into Mb-scale compartments in the nuclear space, distinct from transcriptionally silent regions. More locally chromatin is organized into topological domains, serving as functionally insulated units with cell type – specific regulatory loop interactions. However, molecular mechanisms establishing and maintaining such 3D organization are yet to be investigated. Recent focus on studying chromatin reorganization accompanying cell cycle progression and cellular differentiation partially explained some aspects of 3D genome folding. Throughout erythropoiesis cells undergo a dramatic reorganization of the chromatin landscape leading to global nuclear condensation and transcriptional silencing, followed by nuclear extrusion at the final stage of mammalian erythropoiesis. Drastic changes of genome architecture and function accompanying erythroid differentiation seem to be an informative model for studying the ways of how genome organization and dynamic gene activity are connected. Here we summarize current views on the role of global rearrangement of 3D chromatin structure in erythroid differentiation.